Allied HealthWays - a clinical guidance website for allied health in an integrated health system - Graham McGeoch; Paula Eden (CSIRO Publishing, 2023)
Background and context The Canterbury health system adopted a whole-system approach towards integrated patient care. There was a need to optimise the use of allied health resources, across private and public settings. Assessment of the problem There was no common means for consensus and communication among allied health professions about consistent patient care, and barriers such as a lack of trust existed. This paper describes the implementation and monitoring of Allied Healthways, a website for allied health professionals, set up in 2017 using the HealthPathways approach. Results Over 100 pathways have been published on Allied Healthways, with >13 000 clinicians using the site in Canterbury. Targeted education sessions for allied health professionals, combined with newsletters, raised awareness of new pathways or changes in the system. A survey highlighted the usefulness of Allied Healthways, and the majority of respondents agreed that the site should be available nationwide. Strategies for improvement Development of pathways was found to be a useful mechanism for improving integration in the system. The workgroups and direct meetings engaged allied health professionals and helped achieve local consensus on pathways. They also enabled improvements to be designed and then communicated as a pathway. Lessons learnt Although the patient journey should be consistent, irrespective of their point of contact with the health system, guidance and processes need to be relevant to their target audience. It was essential to write pathways specifically for allied health professionals.